Case Report: Traumatic cardiac arrest due to pericardial tamponade: successful pericardiocentesis with a Shaldon catheter - Schilling, Maximilian; Serra, Alexandre; Skrabal, Christian; Ehrhardt, Harald; Jungwirth, Bettina; Schmid, Sebastian (Frontiers in Pediatrics, 2024)
In this report, we describe the successful resuscitation of a 4-year-old child who suffered a traumatic cardiac arrest during a routine procedure in the operating room. The diagnosis of a sanguineous pericardial tamponade was made by emergency ultrasonography. Consecutive subxiphoid pericardiocentesis with an adult Shaldon catheter led to return of spontaneous circulation. Subsequent thoracotomy and surgical suturing definitively stopped the bleeding from the right ventricle. The combined expertise of all perioperative disciplines was decisive for the patient's survival.